INCREASING THE QUALITY OF FORMING OF SPINNING DETAILS OF ALUMINUM ALLOYS BY CONTROLLING THE RESIDUAL STRESSES IN THEIR SURFACE LAYER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article are analyzed the effect of technological modes and processing parameters on the stress of spinning (cold flow turning) details of aluminum alloys. Аs the object of the study was used a detail of aluminum alloy AMg5, obtained after 3-stage spinning with intermediate heat treatments between the stages. As a control criterion was used non-destructive resistive electro contact method, based on the correlation between the integral electric and mechanical characteristics of metals and alloys – specific conductivity or electrical resistivity within the h-layer of the metal and the amount of deformation in the crystal lattice of the material due to the residual stresses.